Pyramid of Structure, Pengungkapan Transaksi Pihak Berelasi, dan Tata Kelola Perusahan : Indikasi Ekspropriasi - Fadli Fendi Malawat; Sutrisno Sutrisno; Imam Subekti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
The objective of this study is to analyze the effect of company’s ownership through pyramid structure, and related party transaction disclousure, on expropriation practices, with corporate governance as moderating variable. Analytical technique used is hierarchical regression analysis for testing hypotheses developed in this study. Research population is a manufacturing company listed in Indonesia Stock Exchange (IDX) during years 2014-2016, and the sample is selected using purposive sampling method. The results of this study fails to prove effect of company’s ownership through pyramid structure, and related party transaction disclousure on expropriation practices. Furthermore, this study indicates the corporate governance can to increase the level of related party transactions disclosure, but has not been to reduce the expropriation practices caused by company’s ownership through pyramid structure. This study contributes to the theory of agency type II which discusses conflict of interest between controlling and non-controlling shareholders, and especially the problem of information asymmetry, which can be minimized by the role of corporate governance.